Studi Tentang Indeks Massa Tubuh Terhadap Kondisi Fisik Atlet Muaythai Pusat Pelatihan Kabupaten Malang - Baihaqi, Ja'far; Hariyanto, Eko (Sport Science and Health, 2020)
Abstract: The research describes the study of body mass index on the physical condition of muaythai athletes in Malang Regency. Using descriptive quantitative correlational method. The research subjects were 9 athletes. Results: 1) BMI of boys and girls was classified as normal with an average of 66.67%. 2) The relationship of BMI to abdominal muscle strength for men (0.218) is less than (0.811) and girls (-0.987) less than (0.997). 3) The relationship of BMI to male (0.395) arm muscle strength is less than (0.811) and female (-0.277) less than (0.997). 4) The relationship between BMI and the explosive power of boys (0.836) was more than (0.811) and girls (0.999) were more than (0.997). The relationship of BMI to male speed (0.363) is less than (0.811) and girls (0.438) less than (0.997). 5) The relationship of BMI to male endurance (0.234) is less than (0.811) female (0.327) less than (0.997). Conclusion: There is only a relationship between BMI and explosive power, there is no relationship between BMI on abdominal muscle strength, arm muscle, speed and endurance.Â Abstrak: Penelitian menejelaskan studi tentang indeks massa tubuh terhadap kondisi fisik atlet muaythai Kabupaten Malang. Mengunakan deskriptif kuantitatif metode korelasional. Subjek penelitian 9 atlet. Hasil:1) IMT putra, putri tergolong normal rata-rata 66,67%. 2)Hubungan IMT terhadap kekuatan otot perut putra(0,218) kurang dari(0,811) dan putri(-0,987) kurang dari (0,997). 3)Hubungan IMT terhadap kekuatan otot lengan putra(0,395) kurang dari (0,811) dan putri(-0,277) kurang dari (0,997). 4)Hubungan IMT terhadap daya ledak putra(0,836) lebih dari (0,811) dan putri(0,999) lebih dari (0,997). Hubungan IMT terhadap kecepatan putra(0,363) kurang dari (0,811) dan putri(0,438) kurang dari (0,997). 5)Hubungan IMT terhadap daya tahan putra (0,234) kurang dari (0,811) putri(0,327) kurang dari (0,997). Simpulan: Hanya ada hubungan antara IMT terhadap daya ledak, tidak ada hubungan antara IMT terhadap kekuatan otot perut, otot lengan, kecepatan dan daya tahan.